Sharing Experiences and Seeking Connection: Using Facebook as a Form of Social Support for Incarcerated Loved Ones - Tadros, Eman (Crime & delinquency, 2025)
Those with an incarcerated loved one have been shown to experience isolation and difficulty navigating the criminal justice system as well as form connections with others who are experiencing a similar situation. The use of social media allows for individuals to connect with others in similar experiences. For those with an incarcerated loved one, the use of Facebook allows for connection with others who are also navigating incarceration. Posts were collected from a Facebook group “Incarcerated Loved Ones,” with multiple themes emerging. The themes that emerged from the posts are sharing experiences and seeking connection. The codes for sharing experiences include updates on loved ones, negative emotional experiences, and venting. The codes for seeking connection include prayers and good news. Implications and future directions are discussed.